CLINICAL COURSE OF ALCOHOLIC POLYNEUROPATHY AND ALCOHOLIC MYOPATHY OBSERVED IN ALCOHOLISM - Bobir Temirpulotovich, Turayev (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This article aims to explore the most prevalent neurological manifestations associated with alcoholism, including dysmetabolic encephalopathy, central pontine myelinolysis, demyelination of the corpus callosum, alcoholic polyneuropathy, and alcoholic myopathy. Methods: The study examines the potential therapeutic role of drugs containing succinate, focusing on their application in pathogenetic treatment approaches to address these neurological conditions. Results: Key findings indicate that succinate-containing drugs may offer significant benefits in mitigating the pathological effects of alcoholism on the nervous system by targeting specific mechanisms underlying these disorders. Novelty: The article provides novel insights into the therapeutic potential of succinate-based treatments, presenting an alternative strategy for addressing complex neurological disorders linked to chronic alcohol consumption.